Kejadian penyakit bovine ephemeral fever (BEF) pada sapi potong peranakan limousin - Agus Sjafarjanto; Suko Winoto (VITEK : Bidang Kedokteran Hewan, 2014)
This research aims to find out and identify cases of illness Bovine Ephemeral Fever (BEF), as well as how to handle on beef cattle (Limousin Straits), at Soko subdistrict of Tuban District.This research method using observational data retrieval by way of secondary cases of illness Bovine Ephemeral Fever (BEF) at Straits Limousin beef cattle in 2013, annual reports on cases of animal diseases at Soko subdistrict of Tuban District.The research results, obtained a conclusion that the level of the prevalence of disease of Bovine Ephemeral Fever (BEF) as much as 0,54 %, to scatter data disease of Bovine Ephemeral Fever (BEF) in fourteen village at Soko sub-district, indicating the level of events that high in the village of teak and villages Prambon Tergayam, that is, there were six cases in 2013, because geographically, is a hilly area being at two villages indicating low levels of occurrences of a disease Bovine Ephemeral Fever (BEF), which only one case in the village of Menilo, and villages Cekalang, who is mistakenly geogafis is lowland and hot climate.